RETRACTED: Analisis Nilai-Nilai Agama dan Moral Anak Usia Dini dalam Tayangan Film Kartun Upin dan Ipin - Mohammad Fauziddin (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
RETRACTION TO: Fauziddin, M (2020). ANALISIS NILAI-NILAI AGAMA DAN MORAL ANAK USIA DINI DALAM TAYANGAN FILM KARTUN UPIN DAN IPIN. Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini, 11 (01), 55-64. This article has been retracted by Publisher based on the following reason:The Editor of Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini found the double publication in the article publishing due to article's content similarity published in https://obsesi.or.id/index.php/obsesi/article/view/252Syisva, N (2019). ANALISIS NILAI-NILAI AGAMA DAN MORAL ANAK USIA DINI DALAM TAYANGAN FILM KARTUN UPIN DAN IPIN. jurnal obsesi: Jurnal Pendidikan Anak Usia Dini, Vol.3, No.2 (2019). 506-517One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process